A clinical comparison of antibacterial mouth rinses in orthodontic patients - Rafi' A Al-Talib; Baceer A Abdullah; Ali R Al-Khatib (University of Mosul, College of Dentistry, 2004)
This clinical investigation was under-taken to compare the antibacterial activity of two mouth rinses (chlorhexidine diglu-conate 0.2% and phenolic compounds) with salty water (0.9% NaCl) to assess their ability to control plaque and gingival inflammation in conjunction with a normal daily home care in patients with fixed orthodontic appliance. In this clinical trial, 45 patients were randomly divided into three groups; each containing 15 per-sons matched in age and gender, they were instructed to use rinses twice daily for 30 seconds after breakfast and before the bed-time. The gingival and plaque indices were measured according to Silness and Löe for the six teeth at the baseline and two mon-ths after rinses. The results of the study revealed that there is a significant reduction at p < 0.05 after rinsing with phenol and chlorhexidine digluconate for gingival index, while non significant change for salty mouth-wash, and only significant reduction in plaque index for chlorhexidine digluconate mouth rinse and non significant one for phenol and salty mouthwashes. These results support previous published results on the superiority of 0.2% chlorhexidine digluconate when used in conjunction with professional care as an adjunct to routine oral hygiene practice in orthodontic patients.